Posttraumatic growth in adult cancer patients: an updated systematic review - Ramos, Catarina (2018)
The current systematic review is an updated analysis of studies with adult cancer patients, regarding factors associated with posttraumatic growth (PTG), which is defined as perceived positive changes after traumatic event, such as cancer. A systematic review was conducted according to the PRISMA Statement guidelines. Seven electronic databases were searched. Quantitative studies with or without psychosocial group intervention that assessed PTG or similar construct (benefit finding [BF], positive life changes, stress-related growth, growth) as main outcome were included. The initial systematic search yielded 659 papers, published between 2006 and 2015. From those, 81 studies fulfilled the inclusion criteria: 73 studies without intervention and 8 entailing an intervention program. The results suggested that socio-demographic (e.g. age, educational level, household income), clinical (e.g. stage of cancer), cognitive (e.g. intrusiveness, challenge to core beliefs), coping-related (e.g. positive reframing, religious coping) and other psychosocial variables (e.g. social support, optimism, spirituality) are positively associated with PTG. BF is associated with gender, marital status, cancer stage, both cancer and treatment type, positive active coping, positive reappraisal, social support and optimism. Psychosocial group interventions with cancer patients show significant effect on the increase of growth reported (PTG or BF). As conclusion, Growth following a cancer experience is an effect of several variables which might be targeted and promoted in the context of multidisciplinary teams, in hospital and clinical settings. Group interventions are a favorable context to the development of PTG after cancer, but interventions that assess PTG as primary outcome are still needed to evaluate the effect of group on PTG’ facilitation.